2022
DOI: 10.3748/wjg.v28.i37.5457
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of endoscopic ultrasound in the evaluation of small gastrointestinal stromal tumors

Abstract: BACKGROUND Gastrointestinal stromal tumors (GISTs) with a diameter of < 2 cm are called small GISTs. Currently, endoscopic ultrasound (EUS) is widely used as a regular follow-up method for GISTs, which can also provide a preliminary basis for judging the malignancy potential of lesions. However, there are no studies on the accuracy of EUS to assess the malignant potential of small GISTs. AIM To evaluate the efficacy of EUS in the diagnosis and risk assessment of small G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
2
3
0
1
Order By: Relevance
“…However, the cutoff size of small GISTs for endoscopic resection remains controversial. Fang et al investigated the clinical course of small GISTs and demonstrated that a cutoff value of 1.4 cm is appropriate for treatment [ 19 ], and Wang et al proposed that a tumor diameter of 1.45 cm should be the optimal cutoff value for resection, which were consistent with our other retrospective study [ 20 ] which identified that a smaller tumor diameter cutoff (1.48 cm) might have better efficacy in differentiating risk grades. Furthermore, a single-institution retrospective study of 69 patients with EUS-suspected GISTs showed that GISTs > 9.5 mm in diameter are associated with significant progression and that 23% of these patients show significant changes in size after more than 3 years of onset [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, the cutoff size of small GISTs for endoscopic resection remains controversial. Fang et al investigated the clinical course of small GISTs and demonstrated that a cutoff value of 1.4 cm is appropriate for treatment [ 19 ], and Wang et al proposed that a tumor diameter of 1.45 cm should be the optimal cutoff value for resection, which were consistent with our other retrospective study [ 20 ] which identified that a smaller tumor diameter cutoff (1.48 cm) might have better efficacy in differentiating risk grades. Furthermore, a single-institution retrospective study of 69 patients with EUS-suspected GISTs showed that GISTs > 9.5 mm in diameter are associated with significant progression and that 23% of these patients show significant changes in size after more than 3 years of onset [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…However, the cutoff size of small GISTs for endoscopic resection remains controversial. Fang et al investigated the clinical course of small GISTs and demonstrated that a cutoff value of 1.4 cm is appropriate for treatment [19], and Wang et al proposed that a tumor diameter of 1.45 cm should be the optimal cutoff value for resection, which were consistent with our other retrospective study [20] which identified that a smaller tumor diameter cutoff (1.48 cm) might have better efficacy in differentiating risk grades. Furthermore, a single-institution retrospective study of 69 patients with EUSsuspected GISTs showed that GISTs > 9.5 mm in diameter are associated with significant progression and that 23% of these patients show significant changes in size after more than 3 years of onset [21].…”
Section: Discussionsupporting
confidence: 84%
“…These results indicate a substantial improvement in diagnosing gastric mesenchymal tumors with the incorporation of AI technologies. However, the diagnostic performance of AI-assisted EUS models for detecting SETs <2 cm in size was not high compared with that of SETs >2 cm in size [29], which might be because EUS characteristics of GISTs, such as marginal irregularity and cystic changes, are not often clearly discernible in small-sized GISTs [40]. This issue could be explained by previous AI-assisted EUS models focusing solely on the EUS images without considering clinical and endoscopic factors.…”
Section: Discussionmentioning
confidence: 94%
“…Gastric SETs have several clinical characteristics, such as age and tumor location, according to histopathology [20,[40][41][42][43]. Old age and location in the gastric body and fundus…”
Section: Discussionmentioning
confidence: 99%